2008
DOI: 10.1097/rct.0b013e318074fd9d
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Enhancement Between Spin Echo and 3-Dimensional Fast Spoiled Gradient Recalled Acquisition in Steady State Magnetic Resonance Imaging of Brain Metastasis at 3-T Magnetic Resonance Imaging

Abstract: On 3-T magnetic resonance imaging, the enhancement of 3DFSPGR images was less than that of the SE images under the same conditions, but not to a fatal degree, and thin slice 3DFSPGR imaging is therefore considered to be useful for detecting small lesions, when given a high dose of contrast agent and a suitable scanning delay time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 16 publications
2
44
0
1
Order By: Relevance
“…The order of pulse sequences can affect the amount of contrast accumulated in the inflamed nerve over time, which, in turn, can result in the particular pulse sequence erroneously appearing to cause more contrast enhancement than that performed earlier in the scan session. However, according to the dynamic study of the 3D FSPGR sequence by Furutani et al 28 the 3D FSPGR sequence reaches peak enhancement after 60 minutes, which persists for 6 minutes. We obtained the 3D-T1-FFE followed by the 3D-FLAIR with a time delay of 3 and 7 minutes, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The order of pulse sequences can affect the amount of contrast accumulated in the inflamed nerve over time, which, in turn, can result in the particular pulse sequence erroneously appearing to cause more contrast enhancement than that performed earlier in the scan session. However, according to the dynamic study of the 3D FSPGR sequence by Furutani et al 28 the 3D FSPGR sequence reaches peak enhancement after 60 minutes, which persists for 6 minutes. We obtained the 3D-T1-FFE followed by the 3D-FLAIR with a time delay of 3 and 7 minutes, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…7 Other studies reported significantly higher contrast between enhancing lesions and normal brain parenchyma on 2D SE than on other sequences, including IRϪfast SE, 2D GE, MPRAGE, and fast 3D SPGR at 3T. 8,19 Komada et al 17 reported that the CNR of brain metastasis on SPACE was significantly higher than that for MPRAGE at 3T. Consistent with them, we found a greater contrast rate and CNR on SPACE, which resulted in the higher contrast enhancement effect on SE than on GE at 3T.…”
Section: Presumed Mechanisms For the High Detection Rate On Spacementioning
confidence: 98%
“…5,6 Furthermore, because the contrast enhancement effect at 3T is higher than that at 1.5T, several studies have suggested that 3D contrast-enhanced GE images provide higher detectability of small brain metastases than 2D contrast-enhanced SE T1-weighted images when a 3T system is used. 7,8 Although high SAR at 3T makes it difficult to obtain T1-weighted 3D images with an SE-type sequence, recent technologic innovations, including parallel imaging, k-space trajectory, and variable flip angles, have solved the problem. Sampling perfection with application-optimized contrasts by using different flip angle evolutions (SPACE) is one such 3D SE-type sequence available at 3T.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 In these images, a high signal intensity of enhancing blood vessels is a disturbing factor because it can be mistaken for enhancing metastases. The suppression of blood vessel signals may simplify radiologists' reading processes and, in turn, improve their performance.…”
mentioning
confidence: 99%